Evaluación agronómica de dos variedades de fréjol a la aplicación de fertilizantes edáficos en la zona de Fumisa. - Cusme Villacis, Virginia Jarixa (2017)
The investigation "agronomic Evaluation of two varieties of bean to the application of fertilizers edáficos in Fumisa's zone" carried out in the estate "Maria Fernanda" property of the gentleman Antonio Chedraui located Km 25 of the route Quevedo, 103 m.s.n.m, with Latitude: S 0 ° 0°53 ' 35?, Length: W 79 ° 29 ' 27?, Tropical humid climate. The proposed objectives were to determine the agronomic behavior of two varieties of beans in response to fertilization, to evaluate the response of the crop to the application of soil fertilizers that potentiate the yield level and to perform the economic analysis of yield based on the cost of fertilizer treatments. The experimental design Random Complete Blocks with factorial arrangement of 3 * 2. As treatments N + P + K was applied in doses of 50 + 30'30 Kg / ha, and YaraMila Complex 220 Kg / ha and a control without fertilization, in three repetitions. The varieties studied were, Tumbe and Pata de Paloma. The sowing was carried out at a distance of 0.50 x 0.50 m. All the necessary agronomic work was carried out for the development of the crop, fertilization, weed control, irrigation and harvesting. The registered variables were number of plants per useful plot at harvest, height of plant at flowering, number of pods per plant, number of seeds per plant, weight of grains, yield of fresh grain (Kg / ha). After the analysis and interpretation of the results it was concluded that all the variables studied were favorably influenced with the incorporation of the fertilizers since they promote the growth and development of the plant. The Pata variety of pigeon fertilized with Nitrogen, Phosphorus and Potassium, in doses of 50 + 30 + 30 kg / ha, generated more pods than the Tumbe variety and control without fertilizer. The Tumbe variety presented a greater number of grains per plant than Pata de Paloma, while the fertilization with NPK was superior to the Yaramila application, which improved this component of yield. Yield in the Pata de pigeon variety was superior to Tumbe at 470 Kg / ha; while the application of NPK showed an increase of 840 Kg above the control, without fertilizing which generated higher economic income. Key word: YaraMila Complex a new fertilizer on the market.